Licensing of Public Health Pest Control Applicators in Florida - Frederick M. Fishel (EDIS, 2009)
PI-169, a 4-page illustrated fact sheet by Frederick M. Fishel, describes the law governing those who make pesticide applications for wide-area mosquito control or for control of other arthropods of public health significance, including midges, sand flies, dog flies, yellow flies, house flies, etc. Includes sources of additional information. Published by the UF Department of Agronomy, January 2009.